DILEMA TRADISI DAN MODERNITAS TELAAH ATAS “KRITIK NALAR ARAB” MUHAMMAD ABID AL-JABIRI - Izzuddin Washil (Khatulistiwa, 2013)
Al-Jabiri denominated his interpretation project of the Arabic tradition as the Arabic reasoning critique (naqd al-aql al-arabi). The project began from his concern over the present reality of the Arab and Islamic world which arguably is still underdeveloped and his desire to present a new thought methodology as a tool to get out of the slump and awaken to the preferred reality. Al-Jabiri differentiated two traditions, one that refers to the tadwin of Islam as part of Islamic-Arabic tradition and the other referring to and departing from the European Renaissance (modernity). The gap between "what was there" (the traditions of our past) and "what is here" (Western civilization) is growing wide and steep. This condition, according to him, made most of us miss the romanticism of our past, but at the same time there is a desire to break away with that tradition. This is the condition that has spawned "a Split Consciousness" of the Arab society, torn between subjective and objective factors, between the ideological burdens and the objective historical reality which is increasingly far from the ideal progress of modern civilization. In the context of modern-contemporary Arab thought, the tendency of literal-textualist thought, (read: tendency of traditionalism) can in fact be referred — though partly —to the framework bayani reasoning system, as well as other trends in favor of modernity based on burhani reasoning system as something that comes from the outside, that goes through the translation process in the tadwin period. The attraction between the two tendencies of tradition and modernity, according to Al-Jabiri, should be used as the realization of a new tadwin moment, with the new size, standard, and enlightenment, on a single principle: "modernization" (reform of thought, tahdits) requires the fulfillment of the prerequisites of "traditionalization" (back to tradition), and similarly "traditionalization" requires the fulfillment process of "modernization."